Myocardial fibrosis in Eisenmenger syndrome: a descriptive cohort study exploring associations of late gadolinium enhancement with clinical status and survival - Broberg, Craig S (BioMed Central, 2014)
BACKGROUND: A relationship between myocardial fibrosis and ventricular dysfunction has been demonstrated using late gadolinium enhancement (LGE) in the pressure-loaded right ventricle from congenital heart defects. In patients with Eisenmenger syndrome (ES), the presence of LGE has not been investigated. The aims of this study were to detect any myocardial fibrosis in ES and describe major clinical variables associated with the finding. METHODS: From 45 subjects screened, 30 subjects (age 43 ± 13 years, 20 female) underwent prospective cardiovascular magnetic resonance with LGE to quantify biventricular volume and function as well as maximal and submaximal exercise during a single visit. Standard cine acquisitions were obtained for ventricular volume and function. Further imaging was performed after administration of 0.1 mmol/kg gadolinium contrast. Regions of LGE were evaluated qualitatively and quantitatively by manual contouring of identified areas, with total area expressed as a percentage of mass. Patients were followed prospectively (mean follow up 7.4 ± 0.4 years) and any deaths recorded. Patients with LGE findings were compared to those without. RESULTS: LGE was present in 22/30 (73%) patients, specifically in RV myocardium (70%), RV trabeculae (60%), LV myocardium (33%) or LV papillary muscles (30%), though in small amounts (mean 1.4% of total ventricular mass, range 0.16 – 6.0%). Those with any LGE were not different in age, history of arrhythmia, desaturation, nor hemoglobin, nor ventricular size, mass, or function. Exercise capacity was low, but also not different between those with and without LGE. Similarly no significant associations were found with amount of fibrosis. There were five deaths among patients with LGE, versus two in patients without, but no difference in survival (log rank =0.03, P = 0.85). CONCLUSIONS: Myocardial fibrosis by LGE is common in ES, though not extensive. The presence and quantity of LGE did not correlate with ventricular size, function, degree of cyanosis, exercise capacity, or survival in this pilot study. More data are clearly required before recommendations for routine use of LGE in these patients can be made.